Prototype Of An Automatic Control System Using Android For Iot-Based Hydroponic Cultivation - Christian Natanael Tarigan; Moranaian Mungkin; Habib Satria (Sean Institute, 2025)
This paper described develop a prototype of an automatic control system using an Android device for hydroponic cultivation based on the Internet of Things (IoT). This system is designed to monitor and control various important parameters in hydroponic cultivation, such as pH levels, temperature, humidity and nutrient availability in real-time via an Android application. Data from these sensors is sent to the cloud and can be accessed and controlled via an Android device. With this system, users can regulate environmental conditions optimally without having to be physically present, so it is hoped that they can increase efficiency and productivity in hydroponic cultivation. The trial results show that this system is able to operate well and provide a fast response to changes in environmental parameters, so it can be an effective solution for automating the hydroponic cultivation process.